1995
DOI: 10.1099/0022-1317-76-8-2063
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of wild-type and gC-, gE- and gI-deleted mutants of Aujeszky's disease virus in the maxillary nerve and trigeminal ganglion of pigs after intranasal inoculation

Abstract: Aujeszky's disease virus (ADV) is a well known neurotropic virus in pigs. In the present study the mechanism of spread of ADV along the maxillary nerve and the role of the viral envelope glycoproteins gC, gE and gI in this process was examined in pigs. The Ka parental strain of ADV and its gC-, gE-and gI-deleted mutants were inoculated intranasally in pigs, after which virus dissemination in the maxillary nerve and the trigeminal ganglion was monitored at time intervals by means of virus isolation. The parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The correct sorting of HSV-1 to tight junctions is apparently dependent on the cytoplasmic domain of gE (23). Similar to the situation in HSV-1, the PrV gE-gI complex is nonessential for growth in vitro (68), but PrV is impaired in neuropathogenicity after deletion of gE or gI (10,24,61,52,54,56). It has also been shown that deletion of gM in addition to gE and gI results in PrV or equine herpesvirus 1 (EHV-1) progeny that are severely compromised in virus release and cell-to-cell spread of infectivity (6,50).…”
mentioning
confidence: 75%
“…The correct sorting of HSV-1 to tight junctions is apparently dependent on the cytoplasmic domain of gE (23). Similar to the situation in HSV-1, the PrV gE-gI complex is nonessential for growth in vitro (68), but PrV is impaired in neuropathogenicity after deletion of gE or gI (10,24,61,52,54,56). It has also been shown that deletion of gM in addition to gE and gI results in PrV or equine herpesvirus 1 (EHV-1) progeny that are severely compromised in virus release and cell-to-cell spread of infectivity (6,50).…”
mentioning
confidence: 75%
“…We have further demonstrated that wild-type virus (PRV Becker), but not PRV Bartha, injected into neck musculature of a cat replicates efficiently in DRG neurons serving the inoculated muscles (8). Several laboratories have demonstrated that the absence of the gE and gI genes from PRV Bartha accounts for the restricted spread in neurons in a variety of animal models (1,3,10,12,22,25,26,29,31,45). The PRV Bartha strain carries a large deletion in the unique short region of the genome that removes not only the gE and gI coding sequences but also all of the Us9 gene and part of the Us2 coding sequences (27,29,34).…”
mentioning
confidence: 99%
“…These genes encode the envelope glycoproteins E and I (gE and gI, respectively) and an envelope-tegument protein, Us9 (8,10,25,26,31). The gE/gI homologues in alphaherpesviruses are expressed on the infected-cell membrane.…”
mentioning
confidence: 99%